PENINGKATAN KEMAMPUAN MENGANALISIS UNSUR INTRINSIK CERPEN DENGAN MODEL INSIDE OUTSIDE CIRCLE SISWA KELAS XI IPA2 SMA NEGERI 1 POLEWALI KABUPATEN POLEWALI MANDAR - Andriani Andriani (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2016)
This study aimed to describe the increasing ability on the learning process and results to analyze the intrinsic elements of a short story by the model Inside Outside Circle IPA2 class XI student of SMAN 1 Polewali Polewali Mandar. This type of research is a classroom action research. This research data is data learning process and learning outcome data. The data source of this research is the teachers and students of class XI SMA Negeri 1 Polewali IPA2 Polewali Mandar with the number of 29 people. The technique used to collect the data, namely: observation, testing, and documentation. Data were analyzed research process with a qualitative descriptive technique while learning outcome data were analyzed by using quantitative descriptive. The learning process to analyze the intrinsic elements of the first cycle has not yet reached the target set research and the classroom atmosphere less conducive. Second cycle learning process more effective and have reached the target after repairs to problems in cycle I. In the second cycle shows that the general conditions have been conducive learning and students' interest in learning to follow analyze the intrinsic elements of a short story by Inside Outside Circle models is quite large. The results of this study indicate that learning to analyze the intrinsic elements of short stories has increased both in the learning process and learning outcomes. The test results of learning to analyze the intrinsic elements of a short story by Inside Outside Circle models increased. In the first cycle of 58.6% of students received grades ≥75 with an average value of 72.7 and the test cycle II of 79.3% of students received grades ≥75 with an average value of 81.9. The results of the first cycle test that is still less than the target of research that students who scored above learning outcomes 75 to ≥75% can be increased in the second cycle students who received grades ≥75 increased by 20.7% of students